Mobile games and learning interest: for fifth graders in mathematics - Sarifah, Iva; Muhajir, Ahmad; Marini, Arita; Yarmi, Gusti; Safitri, Desy; Dewiyani, Leola (Journal of Education and Learning (EduLearn), 2025)
This study aims to develop a mobile game using the QuizWhizzer application to improve fifth graders’ learning interest in mathematics at Kalibata 04 Elementary School, South Jakarta, Indonesia. The contribution of this study is to enhance the interest in mathematics learning for students in all elementary schools in South Jakarta, Indonesia. This research used the analysis, design, development, implementation, and evaluation (ADDIE) model to develop the product as a systematic approach to instructional development. The experimental design, which helps collect data needed for better decision-making, was utilized for the effectiveness test for fifth graders at Kalibata 04 Elementary School, Jakarta, Indonesia. The results showed that sig (2-tailed) reached 0.000, less than 0.05, meaning there was a significant difference between schooling results in the pretest and posttest data. The N-Gain score obtained in this study was 0.49, so the media developed in this research is compelling enough to increase learning interest in mathematics for fifth-grade elementary school students.